Self-assembled ternary hybrid nanodrugs for overcoming tumor resistance and metastasis - Xu Cheng; Dapeng Li; Jiaxi Xu; Bing Wei; Qin Fang; Longshun Yang; Yanbing Xue; Xin Wang; Rupei Tang (Elsevier, 2021)
Traditional chemotherapy exhibits a certain therapeutic effect toward malignant cancer, but easily induce tumor multidrug resistance (MDR), thereby resulting in the progress of tumor recurrence or metastasis. In this work, we deigned ternary hybrid nanodrugs (PEI/DOX@CXB-NPs) to simultaneously combat against tumor MDR and metastasis. In vitro results demonstrate this hybrid nanodrugs could efficiently increase cellular uptake at pH 6.8 by the charge reversal, break lysosomal sequestration by the proton sponge effect and trigger drugs release by intracellular GSH, eventually leading to higher drugs accumulation and cell-killing in drug-sensitive/resistant cells. In vivo evaluation revealed that this nanodrugs could significantly inhibit MDR tumor growth and simultaneously prevent A549 tumor liver/lung metastasis owing to the specifically drugs accumulation. Mechanism studies further verified that hybrid nanodrugs were capable of down-regulating the expression of MDR or metastasis-associated proteins, lead to the enhanced anti-MDR and anti-metastasis effect. As a result, the multiple combination strategy provided an option for effective cancer treatment, which could be potentially extended to other therapeutic agents or further use in clinical test.